Emergence of Escherichia coli ST131 carrying carbapenemase genes, European Union/European Economic Area, August 2012 to May 2024 - Kohlenberg, Anke; Svartström, Olov; Apfalter, Petra; Hartl, Rainer; Bogaerts, Pierre; Huang, Te-Din; Chudejova, Katerina; Malisova, Lucia; Eisfeld, Jessica; Sandfort, Mirco; Hammerum, Anette M; Roer, Louise; et al. (Euro surveillance, 2024)
Analysis of 594 isolates of Escherichia coli sequence type (ST)131 and its single locus variants carrying carbapenemase genes from 17 European Union/European Economic Area countries revealed acquisition of 18 carbapenemase variants, mainly in ST131 clades A and C. Most frequent were blaOXA-244 (n = 230) and blaOXA-48 (n = 224), detected in 14 and 12 countries, respectively. Isolates carrying blaOXA-244 have increased rapidly since 2021. The increasing detection of carbapenemase genes in the E. coli high-risk lineage ST131 is a public health concern.
Keywords: Escherichia coli Infections; Europe; infekce vyvolané Escherichia coli; mikrobiální testy citlivosti; Escherichia coli; beta-laktamasy; bakteriální proteiny; Bacterial Proteins; lidé; Evropa; Evropská unie; Anti-Bacterial Agents; multilokusová sekvenční typizace; proteiny z Escherichia coli; beta-Lactamases; Microbial Sensitivity Tests; European Union; Multilocus Sequence Typing; antibakteriální látky; Escherichia coli Proteins; Humans